Structural Causes of the “Gender Gap” in Nuclear Security: An Overview - Şebnem Udum (International Journal of Nuclear Security, 2022)
This article elaborates on the discussion from the International Atomic Energy Agency (IAEA) International Conference on Nuclear Security (ICONS) 2020 conference and discusses the reasons for the gender gap between professionals working in nuclear security. It puts forward the structural causes for women's choice of field and the formation of gender biases from the perspective of Political Science. It emphasizes the importance of having role-models for women working in the field and provides recommendations to increase the number of women working in nuclear security.
Keywords: nuclear security; gender; structure